2019
DOI: 10.3390/metabo9080168
|View full text |Cite
|
Sign up to set email alerts
|

NMR Based Metabolomic Analysis of Health Promoting Phytochemicals in Lentils

Abstract: Lentils are a high-protein plant food and a valuable source of human nutrition, particularly in the Indian subcontinent. However, beyond sustenance, there is evidence that the consumption of lentils (and legumes in general) is associated with decreased risk of diseases, such as diabetes and cardiovascular disease. Lentils contain health-promoting phytochemicals, such as trigonelline and various polyphenolics. Fourteen lentil genotypes were grown at three locations to explore the variation in phytochemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The authors attributed the total phenolic content to be inversely associated with rainfall. Rochfort et al (2019) also found the genotype  environment interaction to be significant for total phenolic content in lentils with some cultivars showing a strong environmental effect where as other cultivars had no difference in TPC between locations.…”
Section: Total Polyphenolsmentioning
confidence: 82%
“…The authors attributed the total phenolic content to be inversely associated with rainfall. Rochfort et al (2019) also found the genotype  environment interaction to be significant for total phenolic content in lentils with some cultivars showing a strong environmental effect where as other cultivars had no difference in TPC between locations.…”
Section: Total Polyphenolsmentioning
confidence: 82%
“…In particular, the hulls were found rich in polyphenolics, with levels of them that were variable based on the genotype. Moreover, their composition and concentration showed to be strongly influenced by abiotic effects [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the health benefits of durum wheat-based foods, whole meal lentil flour can be used, not only for the complementary biological value of its proteins with those of wheat and barley but also for the presence of different and complementary phenolic molecules, such as catechin/epicatechin [ 56 ] and alkaloids (i.e., trigonelline) with important associated antioxidant activity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%